Application of Ultrasonic Technology in Flow Measurement System in Irrigation District. Issue 4 (May 2020) - Liu, Qing; Feng, Simin
Abstract: Irrigation area measurement of water volume is to optimize irrigation area water use scheduling, and is the key to realizing irrigation area total water control and irrigation water quota management. In order to improve the management level of irrigation districts, speed up the construction of current irrigation districts, and gradually realize digital irrigation districts, it is imperative to transform the automatic construction of water measurement and water measurement in irrigation districts. This project takes the Erba Main Canal of Fenhe Irrigation District in Shanxi Province as the research site. The ultrasonic equipment installed on the irrigation open channel is used to study the measurement of the non-uniform flow of the open channel. According to the cross-sectional area obtained by the water level, the flow rate is calculated.